Model Property Based Material Balance and Energy Conservation Analysis for Process Industry Energy Transfer Systems - Fumin Ma; Gregory M. P. O’Hare; Tengfei Zhang; Michael J. O’Grady (Energies, 2015)
Conventional historical data based material and energy balance analyses are static and isolated computations. Such methods cannot embody the cross-coupling effect of energy flow, material flow and information flow in the process industry; furthermore, they cannot easily realize the effective evaluation and comparison of different energy transfer processes by alternating the model module. In this paper, a novel method for material balance and energy conservation analysis of process industry energy transfer system is developed based on model property. Firstly, a reconfigurable energy transfer process model, which is independent of energy types and energy-consuming equipment, is presented from the viewpoint of the cross-coupling effect of energy flow, material flow and information flow. Thereafter the material balance determination is proposed based on both a dynamic incidence matrix and dynamic balance quantity. Moreover, the model-weighted conservation determination theorem is proved, and the energy efficiency analysis method is also discussed. Results confirmed the efficacy of the proposed methods, confirming its potential for use by process industry in energy efficiency analyses.